Políticas de desarrollo en el contexto de la migración. Coherencias y contradicciones en el caso de dos programas de codesarrollo de España en Colombia y Ecuador - Lacomba-Vázquez, J; Cloquell-Lozano, A. (Revista Iberoamericana de Estudios de Desarrollo)
The migration incident in development has been focusing a significant part of the debates in the international cooperative sphere. Simultaneously, many different countries have designed in the latest years new policies and introduced programmes orientated to reach a positive effect of migration relating to development. However, these new actions wouldn’t have formed in the frame of a real reconsideration and inspection of connections among migration and development policies. The latest codevelopment policy was planned as a way of solving this shortfall, but their results have been the object of studies of many questions. In this article, it is broached from the policy coherence for development viewpoint two experiences inspired from Spain in Colombia and Ecuador, to show some of these contradictions. The analysis underlying logistics to both devices and the implementation results reveal the divergence between the development original idea and its practice, as well as the trouble to bring together considerably divergent interests.